2013
DOI: 10.1186/1471-230x-13-48
|View full text |Cite
|
Sign up to set email alerts
|

The effect of general anaesthesia on gastric myoelectric activity in experimental pigs

Abstract: BackgroundSurface electrogastrography (EGG) is a non-invasive method for clinical assessment of gastric myoelectrical activity. Different forms of general anaesthesia might have various effects on porcine EGG. The aim of this study was to evaluate the impact of different anaesthetic agents on EGG in experimental pigs.MethodsFour 15-minute EGG intervals were recorded and analysed. A baseline EGG recording was started 20 minutes after intramuscular injection of ketamine and azaperone (periods A and B). Four diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Next dose of 20 mg memantine in the second part induced a prominent drop of the EGG power. In our previous studies, porcine dominant frequency on EGG was fully comparable with the values of healthy humans [13][14][15][16]. We tested different types of anaesthesia previously and found no significant difference [15].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Next dose of 20 mg memantine in the second part induced a prominent drop of the EGG power. In our previous studies, porcine dominant frequency on EGG was fully comparable with the values of healthy humans [13][14][15][16]. We tested different types of anaesthesia previously and found no significant difference [15].…”
Section: Discussionsupporting
confidence: 58%
“…Our current study brings an important new insight into understanding the effect of memantine on gastric myoelectric activity. We used surface electrogastrography (EGG), a non-invasive method for assessment of gastric myoelectrical activity [9][10][11], which gives comparable results in pigs and in healthy humans, both in dominant frequency and EGG power (areas of amplitudes) [13][14][15][16]. In our current study, single dose of memantine significantly increased DF, while repetitively administrated memantine caused important gastric arrhythmia.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Overall outlines of the exteriorised intestines are displayed below each ST map and each ST map is 20 min long (vertical axis). reduced after the administration of anaesthetic (Ailiani et al, 2009;Torjman et al, 2005), whereas, in pigs, the frequency of slow waves varied depending on the type of anaesthetic used (Tachecí et al, 2013). MS222, the general anaesthetic used in this study, has been shown to impair cardiovascular performance in fish (Hill et al, 2002;Houston et al, 1971).…”
Section: Research Articlementioning
confidence: 73%
“…Pigs, as an omnivorous representative, can be used in various preclinical experiments due to their relatively very similar gastrointestinal functions compared to humans (1,2). Our group demonstrated that gastric myoelectrical studies (using electrogastrography) are reliable and feasible in experimental pigs (3)(4)(5)(6)(7). The aim of this current project was to work out our own method of oesophageal manometry in experimental pigs.…”
Section: Introductionmentioning
confidence: 99%